1991
DOI: 10.2343/geochemj.25.31
|View full text |Cite
|
Sign up to set email alerts
|

Non-chondritic yttrium/holmium ratio and lanthanide tetrad effect observed in pre-Cenozoic limestones.

Abstract: REE and Y in limestones have been determined by ICP-AES method coupled with pre-concentra tion chemical procedures. The lanthanide tetrad effect has been clearly observed in the REE patterns of two Permian limestones. It is the W-type tetrad effect seen in seawaters. Y/Ho ratios for the limestones show large positive deviations from the chondritic ratio. Similar non-chondritic Y / Ho ratios are seen in a Precambrian limestone from South Africa, seawaters, and marine phosphorites. Their REE patterns are well ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 25 publications
2
69
0
3
Order By: Relevance
“…The similarity of Y with Ho in ionic size and Kawabe et al (1991) recognized that marine carbonates display nonchondritic Y/Ho ratios (i.e., Y/Ho > 27). Later studies on REE and Y abundances in marine realm by Bau et al (1995) and Nozaki et al (1997) showed superchondritic Y/Ho ratios in sea water.…”
Section: Yttrium Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of Y with Ho in ionic size and Kawabe et al (1991) recognized that marine carbonates display nonchondritic Y/Ho ratios (i.e., Y/Ho > 27). Later studies on REE and Y abundances in marine realm by Bau et al (1995) and Nozaki et al (1997) showed superchondritic Y/Ho ratios in sea water.…”
Section: Yttrium Fractionationmentioning
confidence: 99%
“…Analytical uncertainties arẽ 5% or less. Detailed analytical method for extractions of REE and Y from carbonate matrix is given in Kawabe et al (1991Kawabe et al ( , 1994.…”
Section: Nagaur Ganganagar Basinmentioning
confidence: 99%
“…5); the effect appears to become negligible at about 1200°C. This in turn suggests the possible use of Y/Ho ratios as a geochemical tracer of low-temperature melting (below ~1100°C) processes in petrogenesis and magma source history; however, incorporation of sediment into magma sources could have similar effects due to the strong fractionation of Y from Ho in the marine environment (Kawabe et al, 1991;Nozaki et al, 1997).…”
Section: Factors Other Than Cation Charge and Radius: Y/ho Zr/hf Nb/tamentioning
confidence: 99%
“…The REE and Y pattern has a concave tetrad effect, a large negative Ce anomaly, a small negative Eu anomaly and a high Y/Ho ratio. These are the typical characteristics of REE and Y patterns for marine limestones (Kawabe et al, 1991;Miura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Each run product was dissolved in HCl. The REE and Y in the solution were separated from matrix elements by the method of coprecipitation with Fe(III) oxyhydroxide and cation-exchange chromatography described elsewhere (Kawabe et al, 1991(Kawabe et al, , 1994. Finally they were analyzed by ICP atomic emission spectrometry (ICP-AES) and ICP mass spectrometry (ICP-MS).…”
Section: Introductionmentioning
confidence: 99%